Drug treatments associated with Achilles tendon rupture. A case‐control study involving 1118 Achilles tendon ruptures. (5th September 2018) - Nyyssönen, Timo; Lantto, Iikka; Lüthje, Peter; Selander, Tuomas; Kröger, Heikki
Abstract : The incidence of Achilles tendon (AT) rupture, especially nonsport‐related rupture, is increasing, while the reasons for this increase are largely unknown. The association between the AT rupture and the use of various drug treatments was studied. We collected AT rupture patients from the Finnish Hospital Discharge Register. We also acquired information about all the doctor‐prescribed drugs they had purchased within 1 year before the rupture. For comparison, we randomly selected age‐ and sex‐matched controls from the Finnish Population Register. There were 1118 AT rupture patients. Several drug groups had a statistically significant association with the AT rupture. Our study confirmed an association between fluoroquinolone antibiotics and AT rupture (OR 2.20, P = 0.005). A statistically significant association of renin‐angiotensin II receptor antagonists with tendon rupture (OR 7.59, P = 0.003) was a previously unreported finding. The increasing incidence of AT rupture, especially in middle‐aged and elderly patients, might partially be a consequence of the increased use of certain drug treatments. Some associations are probably explained by the symptomatic treatment of the painful tendon before the rupture.